2017
DOI: 10.1111/ecc.12707
|View full text |Cite
|
Sign up to set email alerts
|

Decreased body mass index is associated with impaired survival in lung cancer patients with brain metastases: A retrospective analysis of 624 patients

Abstract: Body mass index (BMI) is a prognostic factor in several cancer types. We investigated the prognostic role of BMI in a large patient cohort with newly diagnosed lung cancer brain metastases (BM) between 1990 and 2013. BMI at diagnosis of BM and graded prognostic assessment (GPA) were calculated. Definitions were underweight (BMI <18.50), weight within normal range (BMI 18.50-24.99) and overweight (BMI ≥ 25.00). A total of 624 patients (men 401/624 [64.3%]; women 223/624 [35.7%]; median age of 61 [range 33-88]) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 45 publications
2
24
1
Order By: Relevance
“…The presence of anorexia or weight loss in patients with advanced lung cancer is not a new finding. 12 , 20 - 22 However, we have demonstrated that the concomitance of these conditions is an important predictor of shorter survival. Other studies have shown that the presence of these symptoms may result in complications, including reduced tolerance to chemotherapy, as well as decreased mobility and functionality, leading to a worse quality of life and a consequent reduction of survival.…”
Section: Discussionmentioning
confidence: 89%
“…The presence of anorexia or weight loss in patients with advanced lung cancer is not a new finding. 12 , 20 - 22 However, we have demonstrated that the concomitance of these conditions is an important predictor of shorter survival. Other studies have shown that the presence of these symptoms may result in complications, including reduced tolerance to chemotherapy, as well as decreased mobility and functionality, leading to a worse quality of life and a consequent reduction of survival.…”
Section: Discussionmentioning
confidence: 89%
“…6,[12][13][14][15][16][17][18][19] In studies covering both resectable and metastatic lung cancers, the worst outcomes were observed in underweight patients as defined by having a body mass index (BMI) less than 18.5 kg/m 2 . 6,[12][13][14][15][20][21][22][23][24][25][26][27][28][29] Being severely underweight may be an indicator of cancer cachexia, which is a well-described marker of poor outcome on cancer mortality. [30][31][32][33][34][35] Weight in the years before lung cancer diagnosis has also been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Patients of weight gain had better PFS and OS [24]. Another report was retrospectively performed in lung cancer patients with brain metastases, those with high BMI had a better prognosis [25]. The seemingly paradox, or namely obesity cancer paradox, was put-forward in a recent published meta-analysis.…”
Section: Discussionmentioning
confidence: 99%